2007
DOI: 10.1158/1078-0432.ccr-07-1126
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitization by the Histone Deacetylase Inhibitor PCI-24781

Abstract: Purpose: PCI-24781is a novel broad spectrum histone deacetylase inhibitor that is currently in phase I clinical trials. The ability of PCI-24781to act as a radiation sensitizer and the mechanisms of radiosensitization were examined. Experimental Design: Exponentially growing human SiHa cervical and WiDr colon carcinoma cells were exposed to 0.1to 10 Amol/L PCI-24781in vitro for 2 to 20 h before irradiation and 0 to 4 h after irradiation. Single cells and sorted populations were analyzed for histone acetylation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 45 publications
1
31
0
1
Order By: Relevance
“…31 Radiosensitization by PCI24781 has been reported for different cell lines but at much higher concentration than this study. 32 Most importantly, PCI24781 has been shown to decrease RAD51 expression and to inhibit HR, 14 and this is confirmed in the presented data ( Fig. 2A-C).…”
Section: O N O T D I S T R I B U T Esupporting
confidence: 83%
“…31 Radiosensitization by PCI24781 has been reported for different cell lines but at much higher concentration than this study. 32 Most importantly, PCI24781 has been shown to decrease RAD51 expression and to inhibit HR, 14 and this is confirmed in the presented data ( Fig. 2A-C).…”
Section: O N O T D I S T R I B U T Esupporting
confidence: 83%
“…In addition to monotherapy efficacy, some HDACi (including PCI-24781) have synergy with conventional chemotherapy and radiation (19)(20)(21). Consequently, we examined STS cell growth effects of PCI-24781 alone or combined with chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that PCI-24781 is potentially a STS chemosensitizer. HDACi, including PCI-24781, can synergize with DNA-damaging agents (21,22). One potential mechanism underlying such observations is that PCI-24781 can induce blockade of DNA double-strand break homologous recombination repair, at least in part due to down-regulation of Rad51 (23).…”
Section: Resultsmentioning
confidence: 99%
“…The HDAC inhibitors have shown synergistic cell killing for human tumor cell lines with chemotherapeutic drugs (23,24). In addition, several HDAC inhibitors have been reported to enhance cell killing by ionizing radiation in human tumor cells (8,(12)(13)(14)16). In this study, we demonstrated that the HDAC inhibitor scriptaid also sensitized human tumor cells to radiation.…”
Section: Discussionmentioning
confidence: 55%